The Shifting Attitudes of Acehnese towards Rohingya Refugees: Rise of Autochthony? - Raharema, Naufal Rasendriya Apta (Nation State: Journal of International Studies, 2024)
Various rejections by local Acehnese, as well as netizens on social media, have emerged against the newly arrived Rohingya refugees on the beaches of Aceh. The rejection ranges from the locals' rejection of the boats to land to the forced removal of the refugees by students. This change in response from the local Acehnese community is surprising, as the local community's response to the refugees has been known to be positive since the first boat arrived. Through a qualitative analysis that connects the issue with the concept of autochthony, this research found that such concept is connected to the shifting response of the Acehnese towards the newly arrived Rohingya refugees, whereas the concept’s key points of (1) protection of ancestral heritage as well as (2) fear of being contaminated by foreign influences, are prevalent in the locals’ recent gestures and acts of refusals. If this attitude is maintained, it is not impossible that more discrimination towards the Rohingya refugees could take place in the near future.